Impact of the extinct megaherbivore Steller's sea cow (Hydrodamalis gigas) on kelp forest resilience - Roopnarine, Peter D.; Banker, Roxanne M. W.; Sampson, Scott D. (Frontiers in Ecology and Evolution, 2022)
Giant kelp forests off the west coast of North America are maintained primarily by sea otter (Enhydra lutris) and sunflower sea star (Pycnopodia helianthoides) predation of sea urchins. Human hunting of sea otters in historical times, together with a marine heat wave and sea star wasting disease epidemic in the past decade, devastated these predators, leading to widespread occurrences of urchin barrens. Since the late Neogene, species of the megaherbivorous sirenian Hydrodamalis ranged throughout North Pacific giant kelp forests. The last species, H. gigas, was driven to extinction by human hunting in the mid-eighteen century. H. gigas was an obligate kelp canopy browser, and its body size implies that it would have had a significant impact on the system. Here, we hypothesize that sea cow browsing may have enhanced forest resilience. We tested this hypothesis with a mathematical model, comparing historical and modern community responses to marine heat waves and sea star wasting disease. Results indicate that forest communities were highly resistant to marine heat waves, yet susceptible to sea star wasting disease, and to disease in combination with warming. Resistance was greatest among systems with both sea cows and sea otters present. The model additionally predicts that historical communities may have exhibited delayed transitions after perturbation and faster recovery times. Sea cow browsing may therefore have enhanced resilience against modern perturbations. We propose that operationalizing these findings by mimicking sea cow herbivory could enhance kelp forest resilience.